PENGARUH PEMBERIAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN TANAMAN JELAI (Coix lacryma-jobi L.) - Sundari Sundari; Richo Budi Setiawan (Jurnal Magrobis, 2020)
This research aims to determine the influence of cow manure to the growth of barley plants (Coix lacryma-jobi L.). This research began in August to November 2019, located in Bensamar Hamlet, Tenggarong District, Kutai Kartanegara Regency, East Kalimantan Province. The research uses the Randomized Complete Block Design (RCBD) which consists of 6 repeats. Consists of 4 levels, namely K0 (control), K1 (6,25 kg), K2 (12,50 kg), and K3 (18,75 kg). The results showed that the treatment for cow manure gave no significant effect against all observation parameters. The average high yield of the highest crops was obtained at K3 (30 t ha-1) treatment of 99,30 cm. The treatment of cow manure showed no apparent effect on all observation parameters. The average yield of the highest number of leaves is obtained on the K2 (20 t ha-1) treatment of 11,86. The treatment of cow manure showed no apparent effect on all observation parameters. The average yield of the highest rod circumference is obtained at K2 (20 t ha-1) treatment of 8,71 cm.